2001
DOI: 10.1074/jbc.m106710200
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating Hormone Stimulates Protein Kinase A-mediated Histone H3 Phosphorylation and Acetylation Leading to Select Gene Activation in Ovarian Granulosa Cells

Abstract: We examined the phosphorylation and acetylation of histone H3 in ovarian granulosa cells stimulated to differentiate by follicle-stimulating hormone (FSH). We found that protein kinase A (PKA) mediates H3 phosphorylation on serine 10, based on inhibition exclusively by PKA inhibitors. FSH-stimulated H3 phosphorylation in granulosa cells is not downstream of mitogenactivated protein kinase/extracellular signal-regulated kinase, ribosomal S6 kinase-2, mitogen-and stressactivated protein kinase-1, p38 MAPK, phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 98 publications
(55 reference statements)
9
111
1
1
Order By: Relevance
“…Our observation of rapid, cAMP-mediated loss of H3 phosphorylation stands in contrast to that of Salvador and colleagues who reported that cAMP signaling rapidly and transiently induces H3 phosphorylation in primary cultures of ovarian granulosa cells and at cAMP target promoters [11]. Clearly, the response of a given cell to cAMP signaling depends on the array of cyclic nucleotide binding proteins and downstream effectors expressed.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Our observation of rapid, cAMP-mediated loss of H3 phosphorylation stands in contrast to that of Salvador and colleagues who reported that cAMP signaling rapidly and transiently induces H3 phosphorylation in primary cultures of ovarian granulosa cells and at cAMP target promoters [11]. Clearly, the response of a given cell to cAMP signaling depends on the array of cyclic nucleotide binding proteins and downstream effectors expressed.…”
Section: Discussioncontrasting
confidence: 96%
“…An interesting aspect of H3 phosphorylation is its regulation by signal transduction pathways. Phosphorylation of histone H3 at serine 10 has been shown to be increased in mammalian interphase nuclei by the MAP kinase [9], protein kinase A (PKA) [10,11], and NF-κB-cytokine signaling pathways [12,13]. In each case increased H3 phosphorylation was found to occur at particular genes activated by these pathways which suggests a role in regulation of gene expression [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore investigated the phosphorylation of histone H3 on Ser-10, a substrate for several kinases 28,29 , which is known to be regulated by PP1 30,31 . The phosphorylation of H3 on Ser-10 is a key step in nucleosomal response 28,32 and is crucial for memory formation 33 .…”
Section: Nuclear Translocation Of Darpp-32 Is Essential For D1r-regulmentioning
confidence: 99%
“…Besides acetylation of histones, the core histones and histone H1 undergo phosphorylation on specific serine and threonine residues in chromosome condensation during mitosis (Bradbury, 1992;Koshland and Strunnikov, 1996). Phosphorylation of histone H3 N-terminal serine 10 is closely related to both the induction of immediate-early (IE) genes, including proto-oncogenes c-fos and c-jun, and to chromatin remodeling and chromosome condensation during mitosis and meiosis (Wei et al, 1998;Chadee et al, 1999;Sassone-Corsi et al, 1999;Thomson et al, 1999;Clayton et al, 2000;Salvador et al, 2001). In addition, a recent study has shown that phosphorylation of histone H3 at serine 28 also occurs in chromosomes predominantly during early mitosis and coincides with the initiation of mitotic chromosome condensation in various mammalian cell lines (Goto et al, 1999).…”
Section: Introductionmentioning
confidence: 99%